Assessing Early Complications and Surgical Outcomes of Endoscopic Third Ventriculostomy in Obstructive Hydrocephalus: Insights from 128 Cases - Abdul Waheed, Muhammad Aqeel Natt, Ishfaque Ahmed Simair, Syeda Khoula Azmat, Muhammad Imran Khan, Saleem Ahmed Bhutto (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Endoscopic Third Ventriculostomy (ETV) is a well-established treatment for obstructive hydrocephalus, particularly in cases where other interventions, such as shunting, are not ideal. Despite its benefits, early complications remain a concern. This study aims to investigate the frequency and pattern of early complications following ETV in 128 patients with obstructive hydrocephalus. Methods: A retrospective analysis was conducted on 128 patients who underwent ETV for obstructive hydrocephalus at a tertiary care institution between 2015 and 2020. Patient demographics, surgical outcomes, and early postoperative complications (within 30 days of surgery) were assessed. The complications evaluated included infection, bleeding, cerebrospinal fluid (CSF) leakage, stoma obstruction, and neurological deterioration. Results: The overall complication rate was 18.75%. The most common complications were infection (5.5%), CSF leakage (4.5%), and stoma obstruction (4.0%). Infection was primarily characterized by wound infections and ventriculitis. Stoma obstruction was observed in 5 cases, requiring re-operation. Postoperative deterioration of neurological status occurred in 3.9% of patients, while seizures were observed in 2.3% of cases. Conclusion: ETV is a generally safe and effective procedure for treating obstructive hydrocephalus, with a manageable complication rate. Early complications primarily include infection, CSF leakage, and stoma obstruction. Timely detection and appropriate management of these complications can significantly improve postoperative outcomes. Keywords: Endoscopic Third Ventriculostomy, obstructive hydrocephalus, early complications, stoma obstruction, CSF leakage, infection